Post-acute asthma exacerbation care: are we following patients up timely or are we harming them? - Jayden Patel; Irem Karatas; Siva Mahendran (Clinical Medicine)
Introduction: Asthma is the most common lung condition in the UK, affecting 4.3 million adults and costing the NHS £1.1 billion annually.1 Uncontrolled asthma is a major cause of admission to hospital and, in England alone, it led to 34,800 admissions in 2022–2023.2 Of these, 26% were associated with readmission within 90 days, presenting an urgent unmet clinical need.3British Thoracic Society (BTS) guidance and best practices are to review patients within 28 days of their discharge to help optimise asthma management and prevent readmission. However, in many hospitals, including our own, there are no dedicated pathways for patients with asthma, which can lead to missed opportunities to prevent avoidable readmission. Aim and Method: This audit assessed our performance, as a district general hospital, against the national standard requiring respiratory follow-up. We sought to determine whether inadequate implementation of asthma services had led to worse outcomes.Using International Classification of Diseases (ICD)-10 codes for acute asthma, we retrospectively identified all patients admitted for acute asthma at our hospital, over the age of 16 years old, between 1 January and 30 April 2023. Only patients with a primary physician-made diagnosis of acute asthma were included and details around their care and follow-up plans were recorded. Results: Over 3 months, 30 patients were admitted for acute asthma, with a median age of 59 years (24–98); 20 were women and 10 were men. All patients survived to discharge and 26 were assessed to be suitable for local follow-up (four were under the care of respiratory teams at other hospitals). Only 10 patients (38%) were offered follow-up, all of whom were seen, but at a median of 94 days. Of the 30 patients, nine (30%) suffered a further exacerbation of asthma within 90 days and four of them (13%) were readmitted to hospital, resulting in 14 cumulative additional inpatient days; two patients (6.7%) were seen within the target of 28 days, neither of whom suffered a readmission. Conclusion: This audit revealed that patients admitted with acute asthma do not receive timely follow-up and are at risk of avoidable harm. Addressing these gaps through dedicated patient pathways in asthma, together with improved awareness, could help lead to better outcomes in the future.